A TLD-Microdosimeter for aerospace usage: Results relevant to airline pilots undertook long-haul intercontinental flights during March–May 2017. (January 2020) - Mukherjee, Bhaskar; Woda, Clemens; Mares, Vladimir
Abstract: During high altitude long haul flights pilots, cabin crew and passengers are exposed to enhanced level of radiation originating from cosmic ray showers (CRS), produced via the interaction of very high-energy (~GeV) primary protons with the air molecules in Earth's atmosphere. The CRS are composed of energetic particles of diverse species, i.e. neutrons, protons, electrons, muons, pions and photons. Furthermore, the magnitude of aircrew radiation exposure depends on flight altitude and duration, geographical location (latitude), geomagnetic conditions and solar activity (modulation) status. In 1990 the International Commission on Radiological Protection (ICRP) classified airline crewmembers as "radiation workers". A miniature passive microdosimeter (LiBe-14) based on LiF (TLD700) and Beryllium Oxide (BeO) thermoluminescence dosimeter chips emulating a large volume gas-filled Tissue Equivalent Proportional Counter (TEPC) was developed by one of the authors (BM). The LiBe-14 was deployed to assess the integrated ambient dose equivalent of two commercial pilots on long haul intercontinental flights during March–May 2017. The accumulated dose equivalents of 1st (38 y, Female, 148 total block hours) and 2nd (29 y, Male, 149 total block hours) pilots were evaluated to be 565 μSv ± 105 μSv and 738 μSv ± 137 μSv, respectively. The results agreed well within ±20% of simulated data evaluated using the well-known EPCARD (E uropean P rogram Package for the C alculation of A viation R oute D oses) aviation dosimetry code. The implementation of LiBe-14 Microdosimeter in routine long haul, high-altitude commercial flights for the estimation of dose equivalent, average LET and quality factor relevant to impinging cosmic radiation is recommended. Highlights: Microdosimeter (LiBe) based on LiF and BeO TLD. Polystyrene phantom bombarded with 81- 231 MeV protons. TLD cross calibration using a gas-filled TEPC. Dose Equivalent, Average LET, Quality Factor. LiBe-Microdosimeter used in aircrew dosimetry.